Fabrication of Two-Dimensional Bi2MoO6 Nanosheet-Decorated Bi2MoO6/Bi4O5Br2 Type II Heterojunction and the Enhanced Photocatalytic Degradation of Antibiotics - Fengshu Kang; Gaidong Sheng; Xiaolong Yang; Yan Zhang (Inorganics)
This article successfully synthesized a series of Bi2MoO6/Bi4O5Br2 heterojunctions using a two-step solvothermal method followed by calcination, and the photocatalytic activity by degradation of tetracycline hydrochloride (TC) was investigated. Compared with pure Bi4O5Br2 and Bi2MoO6, a series of Bi2MoO6/Bi4O5Br2 heterojunctions exhibit higher photocatalytic activity, which can be attributed to the heterostructures with strong interfacial interaction, improving the charge separation. The 2% Bi2MoO6/Bi4O5Br2 heterojunction shows the best photocatalytic activity under visible light irradiation, which is 1.9 times and 1.8 times that of Bi2MoO6 and Bi4O5Br2, respectively. In addition, cyclic experiments have shown that 2% Bi2MoO6/Bi4O5Br2 heterojunction has high stability, with a degradation efficiency only decreasing by 3% after 5 cycles. From the capture agent experiment and ESR test, it can be seen that ·O2− and h+ are the main active species. A possible photocatalytic mechanism of 2% Bi2MoO6/Bi4O5Br2 heterojunction under visible light irradiation was proposed.